2020
DOI: 10.21037/apm-20-2138
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between abnormal cortical activity in the anterior cingulate gyrus and cognitive dysfunction in patients with end- stage renal disease: a fMRI study on the amplitude of low- frequency fluctuations

Abstract: Background: End-stage renal disease (ESRD) patients often have cognitive dysfunction. The abnormal changes in the brains of ESRD patients are difficult to detect with routine imaging examination. Cognitive performance scales are also not an ideal tool because assessments using these scales can be subjective and might be difficult to administer in some ESRD patients. Functional magnetic resonance has the advantages of non-radiation, multidirectional imaging, good repeatability. Using resting-state functional ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…This might indicate that the altered spontaneous brain activity of the precuneus might affect the psychomotor speed and visuospatial ability of hemodialysis patients. Our results were similar to those of previous studies; Gu et al also found that the MoCA scores were significantly lower in the ESRD group, and the ALFF values of the bilateral anterior cingulate gyri were positively correlated with the MoCA scores ( 37 ). Luo et al found that the relationship between LTT scores and the ALFF values of the bilateral middle temporal gyri and cuneus were negative in peritoneal dialysis patients with ESRD ( 24 ).…”
Section: Discussionsupporting
confidence: 93%
“…This might indicate that the altered spontaneous brain activity of the precuneus might affect the psychomotor speed and visuospatial ability of hemodialysis patients. Our results were similar to those of previous studies; Gu et al also found that the MoCA scores were significantly lower in the ESRD group, and the ALFF values of the bilateral anterior cingulate gyri were positively correlated with the MoCA scores ( 37 ). Luo et al found that the relationship between LTT scores and the ALFF values of the bilateral middle temporal gyri and cuneus were negative in peritoneal dialysis patients with ESRD ( 24 ).…”
Section: Discussionsupporting
confidence: 93%
“…The decreased connectivity between the thalamus and auditory cortex in patients with major depression may lead to mismatched processing at the cortical level, contributing to these patients' clinical symptoms ( 37 ). In addition, the ALFF value in the ACC is significantly reduced in patients with end-stage renal disease (ESRD) and is positively correlated with Montreal Cognitive Assessment (MoCA) scores, suggesting that the ALFF value in this region may be an imaging indicator of cognitive dysfunction ( 38 ). Thus, we speculated that the PACG might lead to the reorganization of auditory and cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior cingulate gyrus is one of the important structures responsible for the executive function of the brain, and it mainly monitors ongoing directional behaviors and coordinates cognitive processes ( 42 ). The medial part of the superior frontal gyrus is commonly deactivated during the cognitive-related processing and has been ascribed to be a component of the default mode network and a study also found that the superior frontal gyrus is anatomically connected with the cingulate cortex (mostly the anterior cingulate gyrus and the mid-cingulate cortex) through resting-state functional connectivity analysis ( 43 ).…”
Section: Discussionmentioning
confidence: 99%